Dealing with diversity: State strategies on ethnic minority management in Southeast Asia - Juliano, Hansley A (Archīum Ateneo, 2019)
Southeast Asia’s ethnic, political and cultural diversity continues to pose major policy and governance hurdles in enforcing a common community born out of the post-colonial nationalist baggage of almost all the region’s countries. ASEAN’s “non-interference” clause gives leeway to each member state to respond to its ethnic diversity with nation-building projects through exclusionary governance. With this leeway, each Southeast Asian country’s nation-building policieslegitimize a particular, existing ethno-nationalist or “ethno-religious” majority at the expense of democratic accountability. This study proposes a preliminary quantitative model which uses regression analysis to compare Southeast Asian countries’ data on their religious and ethnic populations. The initial model categorizes the types of minority management strategies depending on their respective ethnic heterogeneity. This study hypothesizes that a) states with moreethnically homogenous populations will have more exclusionary and violent state policies towards minorities, while b) states with more heterogeneous populations will have fewer exclusionary and violent policies. The results indicate a moderate causality between the two variables and may be correlated with additional variables such as the level of democratic consolidation (as tabulated by the Polity IV democratic index) and the centralized structure of governance.